HUBUNGAN ANTARA KADAR BESI (Fe) AIR TAMBAK TERHADAP KADAR BESI (Fe) PADA DAGING IKAN NILA (Oreochromis niloticus) DAN IKAN BANDENG (Chanos chanos) DI KECAMATAN JABON SIDOARJO - Siti Dzurrotul Ainiyah; Indah Lestri; Ary Andini (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2018)
Jabon sub-district was one of located affected by Lapindo mudflow that had effect in water quality causing environmental pollution. One of the indicators of water pollution was heavy metal Fe exceeded of Fe standard about 0,3mg/L. When Fe was accumulated in the body could make irritation on skin and eyes, respiratory symptom, and could be caused cancer in long term. The purpose of research was to know correlation between Fe levels of pond water with Nile tilapia fish and Milkfish. This research used 10 samples of pond water, Nile tilapia fish and Milkfish were taken at same location in pond area of Jabon Sub-district. Analyzed of Fe was using Atomic Absorption Spectrophotometer (AAS). Based on the result indicated that Fe levels of pond water in Jabon sub-district was lower than Fe standard with mean about 0,015±0,445mg/L. Meanwhile Fe levels of Nile tilapia fish and Milkfish had mean about 4,783±0,444mg/kg and 6,6589±2,845mg/kg those were higher than Fe standard (> 0.5 mg/kg). It could be indicated that fish meat of Nile tilapia fish and Milkfish were contaminated by Fe.Therefore, the results of pearson correlation test were shown no correlation between Fe levels of ponds water with Nile tilapia fish and Milkfish.